The Role of Women Workers in Surabaya, East Java,Indonesia, in Meeting Families’ Needs During the Covid-19 Pandemic: a Maqāṣid Sharīah Perspective - Nur Lailatul Musyafaah; Elda Kusafara; Firda Maknun Hasanah; Anas Bustomi; Hammis Syafaq (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
This research studied the role of women workers in Surabaya in meeting the family’s needs during the Covid-19 pandemic. As field research, it employed a qualitative approach. The data was collected through interviews with 12 women workers and observation at the respondents’ workplaces from November 2021 to April 2022. This research concluded that women workers have a significant role in meeting the family’s needs during the Covid-19 Pandemic. Their role comes in three categories: First, they work to help husbands in meeting primary needs because the husband’s salary cannot cover the whole bill. Second, they work to meet the family’s secondary needs because the husband’s salary is only sufficient for the family's primary needs. Third, they work to meet primary and secondary needs because no one provides so. In the perspective of maqāṣid shariah, their role are according to the principle of maintaining property (ḥifẓ al-māl). The first role is according to the principle of ḥifẓ al-māl in the category maṣlaḥah ḍarūriyyāt. The second role accords to the principle of ḥifẓ al-māl in maṣlaḥa ḥajiyyāt and the third role is according to the principle of ḥifẓ al-māl in maṣlaḥah ḍarūriyyāt and maṣlaḥah ḥajiyyāt.